A case report of all-trans retinoic acid-induced pseudotumor cerebri in an adult patient of acute promyelocytic leukemia - Kapoor, Akhil; Kumar, Narender; Nirban, Raj Kumar; Kalwar, Ashok; Kumar, Harvindra Singh (International Journal of Basic & Clinical Pharmacology, 2017)
All-trans retinoic acid (ATRA), a derivative of vitamin A, is the first line drug for acute promyelocytic leukemia (APL). At the same time, ATRA is also associated with various side effects, including some life threatening conditions. We describe a case of ATRA-induced pseudotumor cerebri in an adult patient of APL.